Nomenclature - specification for a nomenclature system for medical devices for the purpose of regulatory data exchange (ISO 15225:2000 and its amendment 1:2004, IDT) - Department of Standards Malaysia (Malaysia, MY : Department Of Standards Malaysia, 2005)
16